Effect Of Human Resource Management Practices to Maturity Knowledge Management - Sukardi Sukardi; Anik Herminingsih; Djumarno Djumarno; Kasmir Kasmir (Jurnal Doktor Manajemen (JDM), 2021)
Human resources are an asset for the company. Therefore, to get the best employees, human resource management is important to take the first steps in selecting prospective workforce, maintaining, developing, evaluating, and managing employee relations. The purpose of this study was to determine the effect of human resource management practices on knowledge management maturity. This study used a population of 125 education staff (permanent lecturers), with a total sample of 62 respondents or 50% taken. The results showed that human resource management practicesSimultaneously, the effect of 0.59 affects the maturity of knowledge management. However, partially, there are two variables that have a significant effect, namely recruitment and compensation, while the three variables of training and development, performance management and employee relations have a negative influence or do not contribute to the maturity of knowledge management. Keywords : Human Resources Management Practices, recruitment, training and development, compensation, performance management, employee relations, knowledge management.